Impact of the COVID-19 Pandemic on Laboratory Services - Triyani, Yani; Herawati, Rita; Rahmawati, Rahmawati; Permatasari, Ranti (Universitas Islam Bandung, 2023)
The positive impact of the coronavirus disease 2019 (COVID-19) pandemic is that hospital laboratory services are excellent when other services are declining. Aside from molecular biology laboratory (polymerase chain reaction, PCR) services for COVID-19 diagnostics, public demand has dramatically increased. It is a retrospective descriptive study that uses data on the total number and types of results of laboratory examination orders that have been verified from the laboratory information system of a hospital from 2018 to 2022. Data analysis is presented in the frequency of the number and type of results of laboratory examination orders and differences in requests for laboratory services before and during the pandemic since the government established it on March 8, 2020. The total number of laboratory requests between January 2018 and December 2022 was 1,943,539 services. The highest increase in laboratory examination services was in molecular biology (98.4%). As the need for community services increases for the PCR severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) examination, which is used in addition to diagnosing confirmed COVID-19 patients, it is also necessary for the community to conduct tracing if a family member has a COVID infection or travel requirements and follow-up for hospital employee exit tests who contracted COVID-19. In conclusion, the COVID-19 pandemic has positively impacted laboratory performance. There have been changes and an increase in the number and types of laboratory examination services and personal performance and management in laboratories.